THREE POINT RESECTION IN 3D WITH DISTANCES - S., Bektas; Karaahmetoğlu; Yıldırm; Uyar; Yıldırım; Pakel (International Journal of Research -GRANTHAALAYAH, 2018)
In this study, we will consider Three Point Resection in 3D with Distances. This problem is also called Space Resection. The problem of determining the position continues to be the most important problem of geodesy. With the development of measuring instruments and techniques, the widespread use of electronic distance meters, the precise and rapid computation possibilities provided by artificial ground satellites and computers, the segmented approach in the positioning problem (separate calculation of horizontal and vertical coordinates) has left the place as an integrated approach, three dimensional coordinates have begun to be calculated together. The problem of position determination is done either in the form of basic homework or (usually) predictions. It is also possible to calculate the three-dimensional coordinates of the points by the proposed resection method.